Legislative and infrastructural issues in e-commerce and consumer protection in Nigeria - Nuruddeen, Muhammad; Yusof, Yuhanif; Abdullah, Nor Anita (2016)
Electronic commerce or online shopping (e-commerce) is the buying and selling of goods and services via the internet. Those who engage in transactions of this nature are referred to as “electronic consumers” (e-consumers). The success of e-commerce in any given country depends on the existence of relevant legislative framework as well certain infrastructure.Here, the infrastructure includes constant electricity supply, affordable access to electronic devices (computers, laptops, IPad, etc), stable and affordable internet services as well as effective delivery systems of goods and services. This paper, therefore, appraises the legal cum infrastructural issues in e-commerce and consumer protection in Nigeria. The paper adopts a doctrinal research methodology in achieving this task. The paper observes that the Nigerian government is yet to put in place the relevant legislative framework for e-commerce and consumer protection in the country. Thus, the paper emphatically calls for the amendment of the Consumer Protection Act 1992 and immediate passage of Electronic Transactions Bill in Nigeria. Additionally, the paper also observes that consumers in e-commerce transactions encounter a lot of infrastructural challenges in the course of conducting online transactions. Therefore, the paper recommends that the Nigerian government should not only address e-commerce legislative challenges but also ensure adequate provision of the needed infrastructure for consumers to enjoy smooth operation of e-commerce transactions in the country.